The number of adult Eiders in the Baltic Sea (Wildfowl, 2025)
An aerial census of adult male Eiders Somateria mollissima gathered in postbreeding flocks was made in the Baltic Sea on 29 May-5 June 1973. The dense flocks gather at traditional sites soon after the females start to incubate. 271,000 males were counted, mostly from photographs. This figure was corrected to approximately 297,000, including males still in the breeding areas, males migrating south out of the Baltic to Danish moulting areas and underestimations of numbers in flocks seen. The sex ratio was approximately 1:1, both in counts during spring-migration and on the breeding grounds. Thus the number of adult Eiders was about 594,000 specimens, or 297,000 pairs. This figure corresponds roughly with estimates from winter counts and radar studies of north-migration. The method of censusing Eider males in the Baltic, with male counts in postbreeding flocks, is suggested for monitoring purposes.